2015
DOI: 10.1016/j.aap.2014.11.006
|View full text |Cite
|
Sign up to set email alerts
|

Evidence that implementation intentions reduce drivers’ speeding behavior: Testing a new intervention to change driver behavior

Abstract: Implementation intentions have the potential to break unwanted habits and help individuals behave in line with their goal intentions. We tested the effects of implementation intentions in the context of drivers' speeding behavior. A randomized controlled design was used. Speeding behavior, goal intentions and theoretically derived motivational pre-cursors of goal intentions were measured at both baseline and follow-up (one month later) using self-report questionnaires. Immediately following the baseline questi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
39
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(48 citation statements)
references
References 56 publications
(84 reference statements)
9
39
0
Order By: Relevance
“…Consistent with volitional help sheets that have been developed for other social behaviors (e.g., Armitage, 2008Armitage, , 2015, Brewster et al's (2015) volitional help sheet provides participants with a list of 20 separate critical situations in which drivers are known to regularly exceed the speed limit (e.g., Stradling, 2005) and 20 goal-directed responses (strategies for avoiding speeding) that are theoretically derived from Prochaska and DiClemente's (1983) processes of behavior-change. Each critical situation is 2 Consistent with Brewster et al, (2015), an ANOVA focusing only on the participants who were deemed unsuitable for inclusion in the final sample of this study confirmed that there was no difference between the conditions in subsequently measured speeding behavior on the driving simulator, F (3, 85) = 0.64, ns. Also note that a chi-square test showed there was no difference between the conditions in the number of participants who were excluded from the final analysis χ² (3, N = 89) = 1.95, ns.…”
Section: The Implementation Intention Manipulationssupporting
confidence: 60%
See 2 more Smart Citations
“…Consistent with volitional help sheets that have been developed for other social behaviors (e.g., Armitage, 2008Armitage, , 2015, Brewster et al's (2015) volitional help sheet provides participants with a list of 20 separate critical situations in which drivers are known to regularly exceed the speed limit (e.g., Stradling, 2005) and 20 goal-directed responses (strategies for avoiding speeding) that are theoretically derived from Prochaska and DiClemente's (1983) processes of behavior-change. Each critical situation is 2 Consistent with Brewster et al, (2015), an ANOVA focusing only on the participants who were deemed unsuitable for inclusion in the final sample of this study confirmed that there was no difference between the conditions in subsequently measured speeding behavior on the driving simulator, F (3, 85) = 0.64, ns. Also note that a chi-square test showed there was no difference between the conditions in the number of participants who were excluded from the final analysis χ² (3, N = 89) = 1.95, ns.…”
Section: The Implementation Intention Manipulationssupporting
confidence: 60%
“…Consequently, the true effect size of implementation intentions on behavior-change is likely to have been under-estimated in most previous studies. As demonstrated recently by Brewster et al (2015), implementation intentions only reduce speeding for participants who exceed the speed limit more than they intend to. Therefore, only those participants who reported speeding more than they intended to were included in the final sample in this study.…”
Section: Design and Proceduresmentioning
confidence: 76%
See 1 more Smart Citation
“…These interventions may benefit from strategies used to break drivers’ unwanted habits such as implementation intention (if-then plans). 46,47 …”
Section: Discussionmentioning
confidence: 99%
“…By designating a specific if-then contingency between an environment and a plan of action (i.e., if situation X arises, I will perform behavior Y), individuals construct a mental association between a specific situational cue and the appropriate goal-directed behavior response, e.g., 'when accompanied by friends, I will wear my safety helmet when bicycling' instead of 'I will wear my safety helmet' (Baumeister and Vohs, 2004). Research has indicated that this method is effective in translating behavioral intentions into behavior because it allows people to pass control over their behavior to the environmental cues contained in the implementation intention (Brewster et al, 2015;Sheeran and Orbell, 1999).…”
Section: Recommendationsmentioning
confidence: 99%